2015
DOI: 10.3390/bios5030513
|View full text |Cite
|
Sign up to set email alerts
|

Design and Characterization of a Sensorized Microfluidic Cell-Culture System with Electro-Thermal Micro-Pumps and Sensors for Cell Adhesion, Oxygen, and pH on a Glass Chip

Abstract: We combined a multi-sensor glass-chip with a microfluidic channel grid for the characterization of cellular behavior. The grid was imprinted in poly-dimethyl-siloxane. Mouse-embryonal/fetal calvaria fibroblasts (MC3T3-E1) were used as a model system. Thin-film platinum (Pt) sensors for respiration (amperometric oxygen electrode), acidification (potentiometric pH electrodes) and cell adhesion (interdigitated-electrodes structures, IDES) allowed us to monitor cell-physiological parameters as well as the cell-spr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 57 publications
(88 reference statements)
0
32
0
Order By: Relevance
“…Although current research mainly aims at establishing a dynamic culture to increase oxygen supply [14] , we assume that this problem may be less important than the removal of CO 2 to avoid acidification by carbonate. With MC3T3 osteoblasts, we showed that a feeding medium-pH of 7.8 helped uphold the pH above 7.0 in confined microfluidic cell culture systems for longer medium exchange periods [15] . We speculate that elevated pH may provide a simple way to avoid adverse effects on cell proliferation and cell vitality during static cell culturing in 3D scaffolds, not only for osteoblasts.…”
Section: Introductionmentioning
confidence: 92%
“…Although current research mainly aims at establishing a dynamic culture to increase oxygen supply [14] , we assume that this problem may be less important than the removal of CO 2 to avoid acidification by carbonate. With MC3T3 osteoblasts, we showed that a feeding medium-pH of 7.8 helped uphold the pH above 7.0 in confined microfluidic cell culture systems for longer medium exchange periods [15] . We speculate that elevated pH may provide a simple way to avoid adverse effects on cell proliferation and cell vitality during static cell culturing in 3D scaffolds, not only for osteoblasts.…”
Section: Introductionmentioning
confidence: 92%
“…The glass metabolic chip ( Figure 2 B) was a further development of the chip created by Bonk et al [ 51 ]. The microfluidic structure was imprinted in a poly-dimethyl-siloxane (PDMS) layer on the bottom side of a poly-methyl-methacrylate (Plexiglas ® GS, Acrylics Ltd. Niederfischbach, Germany) lid containing four microfluidic ports with tube connectors.…”
Section: Sensorized Glass Chipsmentioning
confidence: 99%
“…After these tests were completed, cell culturing was conducted with the lower left and top right connectors being used as the inlet and outlet, respectively. The inlet and outlet were connected with Teflon (PTFE) tubes to the medium flask and an external peristaltic pump [ 51 ]. The other two connectors were sealed.…”
Section: Sensorized Glass Chipsmentioning
confidence: 99%
“…The analysis of real samples implies the determination of several ions. Analytes of interest are related to acidification, respiration and some ions, such as sodium and potassium among the most general ones [16,17]. Oxygen consumption [18] and acidification [19] are both indicative of cell metabolism.…”
Section: Introductionmentioning
confidence: 99%